Controlling Ligand Substitution Reactions of Organometallic Complexes: Tuning Cancer Cell Cytotoxicity - Wang, Fuyi; Abraha Habtemariam; Erwin P. L. van der Geer; Fernández, Rafael; Michael Melchart; Robert J. Deeth; Rhona Aird; Sylvie Guichard; Francesca P. A. Fabbiani; Patricia Lozano-Casal; Iain D. H. Oswald; Duncan I. Jodrell; et al. (Proceedings of the National Academy of Sciences - PNAS, 2005)
Organometallic compounds offer broad scope for the design of therapeutic agents, but this avenue has yet to be widely explored. A key concept in the design of anticancer complexes is optimization of chemical reactivity to allow facile attack on the target site (e.g., DNA) yet avoid attack on other sites associated with unwanted side effects. Here, we consider how this result can be achieved for monofunctional "piano-stool" ruthenium(II) arene complexes of the type $[(\eta^6-arene)Ru(ethylenediamine)(X)]^{n+}$. A potentially important activation mechanism for reactions with biomolecules is hydrolysis. Density functional calculations suggested that aquation (substitution of X by H2O) occurs by means of a concerted ligand interchange mechanism. We studied the kinetics and equilibria for hydrolysis of 21 complexes, containing, as X, halides and pseudohalides, pyridine (py) derivatives, and a thiolate, together with benzene (bz) or a substituted bz as arene, using UV-visible spectroscopy, HPLC, and electrospray MS. The x-ray structures of six complexes are reported. In general, complexes that hydrolyze either rapidly {e.g., X = halide [arene = hexamethylbenzene (hmb)]} or moderately slowly [e.g., X = azide, dichloropyridine (arene = hmb)] are active toward A2780 human ovarian cancer cells, whereas complexes that do not aquate (e.g., X = py) are inactive. An intriguing exception is the X = thiophenolate complex, which undergoes little hydrolysis and appears to be activated by a different mechanism. The ability to tune the chemical reactivity of this class of organometallic ruthenium arene compounds should be useful in optimizing their design as anticancer agents.